POTENTIAL RISK OF BRAIN DAMAGE AND POOR DEVELOPMENTAL OUTCOMES IN CHILDREN PRENATALLY EXPOSED TO SARS-COV-2: A SYSTEMATIC REVIEW - Leyser,Marcio (2022)
ABSTRACT Objective: To perform a systematic literature review to analyze existing data on the neurological effects of coronavirus on newborns. Data sources: We followed the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P), and searched the PubMed and Embase platforms for the keywords [brain damage OR pregnancy OR developmental outcomes] and [coronavirus OR SARS-CoV-2 OR SARS-CoV OR MERS-CoV] between January 1, 2000 and June 1, 2020. Data synthesis: Twenty-three reports described the course of pregnant women exposed to SARS-CoV-2, SARS-CoV, or MERS-CoV during the gestational period, eight to SARS-CoV-2, eight to SARS-CoV, and seven to MERS-CoV. No data were found on abnormalities in brain development or on a direct link between the virus and neurological abnormalities in the human embryo, fetus, or children. Spontaneous miscarriage, stillbirth, and termination of pregnancy were some complications connected with SARS/MERS-CoV infection. SARS-CoV-2 is not currently associated with complications in the gestational period. Conclusions: The literature has no data associating exposure to coronavirus during pregnancy with brain malformations and neurodevelopmental disorders. However, despite the lack of reports, monitoring the development of children exposed to SARS-CoV-2 is essential given the risk of complications in pregnant women and the potential neuroinvasive and neurotropic properties found in previous strains.